Study on the long-term performance of shield tunnel passing through the gas-bearing strata - He, Jie; Wei, Xiangyang; Yin, Mei (Underground Space, 2023)
When the shield tunnel passes through the gas-bearing strata, gas and water leakage may occur depending on the sealing performance of the segment joints. This process involves the complex multiphase seepage flow phenomenon in unsaturated soil. In this study, a fully coupled solid-liquid-gas model of the GIL Utility Tunnel was established to investigate the influence of the high-pressure gas on the mechanical properties of the tunnel segments and joints. The constitutive model of the Extended Barcelona Basic Model was implemented to simulate the effect of the seepage process on soil deformation. The results show that significant upward displacement occurred in the gas reservoir and its overlying strata, and the maximum displacement reached 30 mm. In addition, during the leakage of the gas and the water, an increase in the average soil effective stress was observed. It would induce a reduction in the suction and expansion of the yield surface. The tunnel tended to be stable from 20 years onwards, thus the soil deformation due to the water leakage only occurred at the early stage. In addition, the joint opening under the most unfavorable internal force combination was 0.69 mm, and the corresponding bolt stress was 119.5 MPa, which is below the yield limit. The results of this study help to understand the influence of high-pressure gas on tunnel safety and the sealing performance of the joints.
Keywords: Infolettre; Infolettre_Juin_2023

Geomechanical Properties of Deep-Sea Pore-Filled Methane Hydrate-Bearing Soils at Critical State Using DEM Analysis - He, Jie; Li, Tao; Rui, Yi (Fractal and Fractional, 2023)
The recognition of the geomechanical properties of methane hydrate-bearing soil (MHBS) is crucial to exploring energy resources. The paper presents the mechanical properties of a pore-filled MHBS at a critical state using the distinct element method (DEM). The pore-filled MHBS was simulated as cemented MH agglomerates to fill the soil pores at varying levels of methane hydration (MH) saturation. A group of triaxial compression (TC) tests were conducted, subjecting MHBS samples to varying effective confining pressures (ECPs). The mechanical behaviors of a pore-filled MHBS were analyzed, as it experienced significant strains leading to a critical state. The findings reveal that the proposed DEM successfully captures the qualitative geomechanical properties of MHBS. As MH saturation increases, the shear strength of MHBS generally rises. Moreover, higher ECPs result in increased shear strength and volumetric contraction. The peak shear strength of MHBS increases with rising MH saturation, while the residual deviator stress remains mainly unchanged at a critical state. There is a good correlation between fabric changes of the MHBS with variations in principal stresses and principal strains. With increasing axial strain, the coordination number (CN) and mechanical coordination number (MCN) increase to peak values as the values of MH saturation and ECPs increase, and reach a stable value at a larger axial strain.
Keywords: Infolettre; Infolettre_Octobre_2023

Benefit of assimilating satellite all-sky infrared radiances on the cloud and precipitation prediction of a long-lasting mesoscale convective system over the Tibetan plateau - He, Jie; Ma, Xulin; Chen, Xingchao (Quarterly Journal of the Royal Meteorological Society, 2023)
Heavy rainfall events in the warm season (May–September) over the Tibetan Plateau (TP) region and its downstream areas are often closely related to eastward-propagating Tibetan Plateau Vortices (TPVs). Hence, improving the prediction of TPVs and their associated convective activity is of paramount importance, given the significant potential impacts they can have on densely populated downstream regions, including but not limited to flooding and damages. In this study, a typical long-lived TPV that occurred in July 2008 was used for the first time to explore the benefit of assimilating satellite all-sky infrared radiances on the cloud and precipitation prediction of the TPV-induced eastward-propagating mesoscale convective system (MCS). The all-sky infrared radiances from the water vapor (WV) channel of the geostationary Meteosat-7 and other conventional observations were assimilated into a 4-km grid spacing regional model using the ensemble Kalman filter. The results revealed that the all-sky infrared data assimilation improved the cloud, precipitation, dynamical, and thermodynamical analyses as well as 0–12-hr deterministic and ensemble forecasts. Compared with the experiment in which the all-sky infrared radiances were not assimilated (non-radiance experiment), the experiment with assimilated all-sky infrared radiances yielded clearly improved initial wind and cloud fields, 1–12-hr cloud forecasts, and 1–6-hr precipitation forecasts. This study indicates that assimilation of all-sky satellite radiances has the potential for improving the operational cloud and precipitation forecasts over the TP and its downstream areas.
Keywords: Infolettre; Infolettre_Septembre_2023

Statistical Damage Constitutive Model for Anhydrite Rock under Freeze–Thaw Cycles Considering the Residual Strength and Postpeak Stress Dropping Rate - Hou, Chao; Jin, Xiaoguang; He, Jie; Li, Hanlin (International Journal of Geomechanics, 2023)
Keywords: Infolettre; Infolettre_Avril_2023; Infolettre_Mai_2023

Do civil engineering fronts emerge from interdisciplinary research? - He, Jie; Yao, Junlan; Chen, Xin; Liu, Fang; Zhu, Hehua (Frontiers of Structural and Civil Engineering, 2023)
Abstract Interdisciplinary research is considered a source of innovativeness and creativity, serving as a key mechanism for creating recombination necessary for the evolution of science systems. The aim of this study is to quantitatively establish the connection between interdisciplinary research and the research fronts that have recently emerged in civil engineering. The degree of interdisciplinarity of the research fronts was measured by developing metrics from bibliographic analyses. As indicated by the consistent increase in the metrics of interdisciplinarity over time, research fronts tend to emerge in studies with increasing diversity in the disciplines involved. The active disciplines involved in the fronts vary over time. The most active disciplines are no longer fundamental but those associated with energy, environment, and sustainable development, focusing on solutions to climate change and integrating intelligence technologies.
Keywords: Infolettre; Infolettre_Fevrier_2023

Numerical and experimental analyses of methane leakage in shield tunnel - He, Jie; Zhu, Hehua; Wei, Xiangyang; Jin, Rui; Jiao, Yaji; Yin, Mei (Frontiers of Structural and Civil Engineering, 2023)
Abstract Tunnels constructed in gas-bearing strata are affected by the potential leakage of harmful gases, such as methane gas. Based on the basic principles of computational fluid dynamics, a numerical analysis was performed to simulate the ventilation and diffusion of harmful gases in a shield tunnel, and the effect of ventilation airflow speed on the diffusion of harmful gases was evaluated. As the airflow speed increased from 1.8 to 5.4 m/s, the methane emission was diluted, and the methane accumulation was only observed in the area near the methane leakage channels. The influence of increased ventilation airflow velocity was dominant for the ventilation modes with two and four fans. In addition, laboratory tests on methane leakage through segment joints were performed. The results show that the leakage process can be divided into “rapid leakage” and “slight leakage”, depending on the leakage pressure and the state of joint deformation. Based on the numerical and experimental analysis results, a relationship between the safety level and the joint deformation is established, which can be used as guidelines for maintaining utility tunnels.
Keywords: Infolettre; Infolettre_Octobre_2023

Trinity flame retardant with benzimidazole structure towards unsaturated polyester possessing high thermal stability, fire-safety and smoke suppression with in-depth insight into the smoke suppression mechanism - Li, Zhen; Fu, Teng; Guo, De-Ming; Lu, Jia-Hui; He, Jie-Hao; Chen, Li; Li, Wen-Da; Wang, Yu-Zhong (Polymer, 2023)
Keywords: Infolettre; Infolettre_Juin_2023